Inclusão : lazer e participação social sob o olhar de pessoas com deficiência mental e suas famílias - Martinelli, Siliani Aparecida (Universidade Federal de São Carlos, 2008)
The history of deficiency was always made by an exclusion way. However, there were movements as integration and inclusion that have contributed to change the rights and conditions of people with deficiency. Besides all efforts of researchers to give a concept that deficiency is due to both social and cultural conditions, determined by society, the meaning of mental retardation remains as personal problem, without social context and no social sense. The participation of adult mental retarded people in their community in leisure activities, as well as places that allow sharing experiences with their peers must contribute to live together, to practice citizenship and to facilitate changes on deficiency representation, altering segregation attitudes and to develop public policies by according with an inclusive society model. In order to answer those question the objectives of this research is to identify and analyze the social participation of the adults with mental retardation, related to places, leisure activities, and also the perception of the family in this process. The approach was qualitative, using half-structured interview that was analyzed by content analysis method. The results showed lack of opportunities, lack of self-determination, no or few options to choice leisure activities among adults with mental retardation and familial over protection giving these people difficulty in participation and autonomy within that social context.
Keywords: Inclusão social; Educação especial; Lazer; Família; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL